Upaya Meningkatkan Aktifitas dan Hasil Belajar Kimia Peserta Didik dengan Penggunaan Peta Konsep Melalui Pembelajaran Kooperatif Tipe STAD Di SMK Negeri 1 Karawang - Suharyanti, Prapti (Persatuan Guru Republik Indonesia (PGRI) Daerah Khusus Ibukota Jakarta, 2018)
ABSTRACT: The purpose of this study was to determine the increase in activities and learning outcomes of chemistry of students by using concept maps through STAD type cooperative learning at SMK Negeri 1 Karawang. The method used was action research or class action. The sample used in this study is class X TP 1 with 32 students. Data collection techniques used were observation and tests. The results of this study indicate that the average activity desired (On Task) students in the first cycle amounted to 52.92, the second cycle was 65.83 and in the third cycle was 73.75. The average activity that is not desired (Off Task) of students in the first cycle is 53.75, the second cycle is 38.33 and the third cycle is 26.67. This data shows that the use of concept maps through STAD type cooperative learning is able to increase the desired activities (On Task) of students (an increase of 20.8%). From the data the learning results obtained that the average test scores of students in the first cycle amounted to 73 , 99 (with learning completeness 67.44), cycle II was 75.95 (with mastery learning 72.45, cycle III was 77.16 (learning completeness was 76.35) .This data shows that the use of concept maps through cooperative learning STAD type is able to improve learning outcomes of students' chemistry subjects. In the third cycle data obtained increases the activity of participants the average learning outcomes of students have achieved the success indicators that have been set before the study was conducted. Thus the next cycle does not need to be done.